Pengaruh Coworker Support dan Supervisor Support Terhadap Work Engagement Melalui Meaningful Work Pada Barista Coffee Shop X - Dewi Masyitha Al Faizah (Jurnal Ilmu Manajemen, 2022)
The purpose of this study are to determine and analyze the impact of coworker support and supervisor support on work engagement through meaningful work. This study uses a type of cross-sectional study that uses quantitative data. The sampling technique using purposive sampling. The number of respondents are 120 baristas of coffee shop x. This study uses Structural Equation Modeling (SEM) with Smart PLS 3.3 software for statistical analysis. The results showed that coworker support has a positive impact but no significant on work engagement. Supervisor support has a positive and no significant impact on work engagement. However, coworker support and supervisor support have significant indirect effect on work engagement, that mediated by meaningful work. The implications of this research are the way work support that employees get will lead them to feel more recognized and valued in their work. Supervisors can act as coaches and provide assistance to employees at work. as well as through giving rewards to stores that have good relationships between co-workers. This will certainly make employees feel facilitated and get comfortable at work.